Marked bleeding diathesis in patients with platelet dysfunction due to a novel mutation in RASGRP2, encoding CalDAG-GEFI (p.Gly305Asp). (2nd January 2018) - Bermejo, Emilse; Alberto, Maria F.; Paul, David S.; Cook, Aaron A.; Nurden, Paquita; Sanchez Luceros, Analia; Nurden, Alan T.; Bergmeier, Wolfgang
ABSTRACT: Congenital platelet function disorders are often the result of defects in critical signal transduction pathways required for platelet adhesion and clot formation. Mutations affecting RASGRP2, the gene encoding the Rap GTPase activator, CalDAG-GEFI, give rise to a novel, and rare, group of platelet signal transduction abnormalities. We here report platelet function studies for two brothers (P1 and P2) expressing a novel variant of RASGRP2, CalDAG-GEFI(p.Gly305Asp). P1 and P2 have a lifelong history of bleeding with severe epistaxis successfully treated with platelet transfusions or rFVIIa. Other bleedings include extended hemorrhage from minor wounds. Platelet counts and plasma coagulation were normal, as was αIIbβ3 and GPIb expression on the platelet surface. Aggregation of patients' platelets was significantly impaired in response to select agonists including ADP, epinephrine, collagen, and calcium ionophore A23187. Integrin αIIbβ3 activation and granule release were also impaired. CalDAG-GEFI protein expression was markedly reduced but not absent. Homology modeling places the Gly305Asp substitution at the GEF-Rap1 interface, suggesting that the mutant protein has very limited catalytic activity. In summary, we here describe a novel mutation in RASGRP2 that affects both expression and function of CalDAG-GEFI and that causes impaired platelet adhesive function and significant bleeding in humans.